Crispy Nori / Nur Najwa Mohamad Hassan Azhari - Mohamad Hassan Azhari, Nur Najwa (2021)
Crispy Nori Sdn Bhd is a Sole proprietorship company based in the capital state of Selangor which is Shah Alam.Crispy Nori Sdn Bhd expects to be one of local seaweed snacks that can catch interest of any age of communities. Our company plans to build a strong market position in the town and also village area. Crispy Nori Sdn Bhd is officially registered with Go-Ecommerce. This company is manage by Nur Najwa as the founder of product. Due to their skills and past experience in the business industry with addition knowledge gained from professional courses attended and by using the online social media, which is Facebook Page as platform to run the business, its help in gained the trust to manage the business. This platform is used because this is one of strong and popular platform to run business among the potential customers. The company get agreement with local factory that manage the Crispy Nori product production from the ingredient of snacks until packaging and using delivery courier services for delivery process. All the best ingredient for seaweed and every process will chose preferably to get the best in every packs of Crispy Nori snacks. This product is the combination of seaweed and two trendy flavour which is cheese and chili flavour. Therefore, for our target and potential customer for this products is among young people, student university, adults and working people who needed food that easy to eat, fast and easy handle and bring and also satiate even its just a pack of snacks. For competitor, Crispy Nori Sdn Bhd compete with several competitors among the snacks industry. All the competitors, local and overseas brand that based in Malaysia have their own strategy and experience in running snacks food industry of business. Therefore, Crispy Nori will make sure can compete comparable with all the competitors’ brands in Malaysia. All the marketing plan that helps in grown brands of business and be one of favourable seaweed snacks that always be the choices among Malaysian and overseas market. Lastly, for the sales revenue of Crispy Nori, business will aim generate more than RM 10,000 for a month in every online sales that using Facebook page for the first years of business. For second years, the aims will continue growth with higher revenue with the involvement and agents, dropship and collaboration with others store in the future. Then, with the increment of revenue sales in the business, additional staff will occur to streamline business so that it is more systematic and effective and be of successful snacks food industry business.